Endovascular repair of thoracic aortic disease with isolated left vertebral artery and unfavorable proximal landing zone using fenestrated castor stent-graft - Wang, Zhenhua; Fang, Changcun; Song, Han; Wei, Duoliang; Meng, Xiangbin; Bai, Xiao; Liu, Chunxiao; Zhao, Xin (Frontiers in Cardiovascular Medicine, 2023)
Objective The main purpose of this study was to evaluate the safety and efficacy of Castor single-branched stent-graft combined with fenestrated technique in treatment of thoracic aortic disease (TAD) with unfavorable proximal landing area (PLZ) and isolated left vertebral artery (ILVA). Methods From January 2018 to March 2022, 8 patients with TAD (6 patients with type B aortic dissections, 1 patient with type B intramural hematomas, and 1 patient with thoracic aortic aneurysm) underwent thoracic endovascular aortic repair with fenestrated Castor stent-graft due to the existence of ILVA and unfavorable PLZ. Demographic characteristics, surgical details, postoperative complications, follow-up and postoperative CTA imaging results were collected and analyzed. Results The primary technical success rate was 100%. The mean operation time was 115 min (range, 70–180 min). All the left subclavian arteries (LSAs) and ILVAs of the eight patients were revascularized by fenestrated Castor stent-grafts. During the follow-up period, no deaths and complications were observed. No internal leakage, aortic rupture, retrograde type A dissection were found on computed tomography angiography. All of the LSAs and ILVAs maintained patency without stenosis. Conclusion Castor single-branched stent-graft implantation combined with fenestration technique may be safe and feasible for TAD patients with ILVA and unfavorable PLZ.